Sítio Arqueológico Abrigo Capivara I(abrigo RS-C-43: resgate de sua história e a contribuição pedagógica para as escolas da rede municipal e estadual de Lindolfo Collor - Presser, Marcos Marcio (2023)
The present work deals with the study of Heritage Education, having as concentration area Architecture and Material Heritage and Research Line Archaeology and paleontology and as a guide the Archaeological Site RS-C-43, Sheltered Capivara I, located in the municipality of Lindolfo Collor. This site, of great historical – cultural and material value which will serve as a reference for the elaboration of a pedagogical game that will be made available to students of the municipal and state education network of this city. This assignment was developed through bibliographic research, which brings as a guiding line a theoretical framework, on education, heritage and pedagogical virtual games. Two surveys were also conducted through virtual questionnaires for teachers in the city, through the google form platform. In the researches it was analyzed about the knowledge of cultural – historical heritage and the interest and knowledge for virtual games. In this way, it is possible to conclude that the preservation of heritage culture is very relevant for the preservation of local identity and memory. Therefore, it is essential that teachers work the material and intangible heritage in the school environment. The archaeological trail will be another pedagogical support to foster cultural heritage appreciation.